1959
DOI: 10.1002/pol.1959.1203913544
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of polyvinyl alcohol by ceric ion

Abstract: The rate of reaction of ceric nitrate with the 1,2‐glycol units and the alcohol units of polyvinyl alcohol was determined at 20°C. It was found that the glycol units are oxidized much faster than the alcohol units even though they are outnumbered about one hundred to one in the polymer chain. Under the conditions studied, at least 83 glycol units reacted per 100 hours oxidized. Since the oxidation of the glycol units is accompanied by chain splitting, the free radicals are produced predominantly at the fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

1961
1961
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…reagent-grade, were used after standardization with ferrous sulfate according to a method described by Mino et al 28 Acrylonitrile monomer was freshly distilled before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…reagent-grade, were used after standardization with ferrous sulfate according to a method described by Mino et al 28 Acrylonitrile monomer was freshly distilled before use.…”
Section: Methodsmentioning
confidence: 99%
“…The consumption of CeIV by cellulose during grafting and oxidation was determined according to a method reported by Mino et al 28 The copper number was determined according to Braidy's method,29 and carboxyl groups were estimated according to the Indian standard method." Figure 1 shows the per cent grafting yields on the various substrates at 40°C.…”
Section: Methodsmentioning
confidence: 99%
“…It has been postulated that the initiation of free radicals on the cellulose molecule occurs through a single-electron transfer according to a mechanism proposed by Mino and Kaizerman. 5 This mechanism favors grafting much more than homopolymer formation. Cleavage of the C2-C3 glycol bond occurs during this system of grafting initiation.…”
Section: Introductionmentioning
confidence: 99%
“…a t room temperature. The analysis was carried out according to the ferrous ammonium method using an o-phenanthroline indicator re- ported by Mino et al 7 The results are shown in Tables 1 and 11. It was observed that ceric ions were apt to be remarkably reduced by aldehyde and alcohol and almost unaffected in acetone or water.…”
Section: Choice Of the Solvent Used For Graft Copolymerizationmentioning
confidence: 99%